The search for safety: The effects of conflict, poverty and ecological influences on migration in the developing world - Raleigh, Clionadh (Global environmental change, 2011)
► The coping mechanisms that allow for sustained existence on degraded lands are strained by conflict. ► The absolute numbers of international migrants is likely to stay relatively low. ► The chronically vulnerable are in places with persistent political violence, poverty and ecological instability. ► Growing populations experience rising urban poverty, ecological variation and livelihood insecurity. ► Typical safety values, including fleeing to neighbouring states, are curtailed by containment policies. This article discusses how conflict patterns affect the volume, direction and types of migration within the developing world. Conflict impact and poverty are the two primary drivers directly shaping migrations within poor and high-risk environments. Indirect drivers of migration include livelihood fragility, ecological and political instabilities. Conflicts overwhelmingly occur in states where much of the population is dependent upon the environment/natural resources for their livelihoods. There is little reliable evidence to suggest a link between civil conflict and climate change, however, the environmental changes occurring across developing states shape the ways in which civilians can respond to political and economic threats. The crucial point is that the communities who are subject to increasing environmental variation and disruption, through either external or internal processes, are likely to become poorer as a consequence. This poverty lessens their ability to respond to the myriad of threats in their environs, including conflict, ecological disasters, disease, or economic hardship. Hence, there is an endogeneity to conflict, precipitating factors and possible outcomes: the persistence of violence plays a determining role in the sustainability of livelihoods, poverty levels and the propensity of migration within chronically conflicted areas. Those most vulnerable to forced migration live in ‘chronically vulnerable areas’, which are characterized by the deterioration, loss or destruction of primary livelihood systems and productive assets, environmental degradation and deterioration of natural resources, increasing impoverishment of communities and households, geographical isolation and a dependence on relief.